Avaliação científica e subjetividade: o “artigo-comprimido” como síntese de uma produção científica alienante: (Management and Connections Journal, 2022)
In view of the changes in recent years in the field of scientific evaluation, the objective of this article is to discuss the effects of CAPES 'current scientific evaluation policies on the subjectivity of public researchers in Administration. The qualitative study was carried out with 13 researchers with a high index of publication. The statements were analyzed based on Bakhtin's philosophy of language. The results show that, in relation to the scientific evaluation, there are aspects of the disposal the researchers alienation that are invisible, such as the intensification of the work and the excessive emphasis on the publication, which is systematically reproduced and validated by the subjects. It is concluded that the desire and commitment of researchers to meet the evaluation criteria guide academic production. There is also a reduction in the exercise of autonomy and the political and social dimension of reflection in the Academy.